Does Methylphenidate Work in Children and Adolescents with Attention Deficit Hyperactivity Disorder? - Johanne Pereira Ribeiro (Pediatric Reports, 2021)
Objective: Attention deficit hyperactivity disorder (ADHD) is a common psychiatric disorder diagnosed in increasing proportions of children and adolescents. The psychostimulant methylphenidate has been considered the first-line pharmacological treatment for children and adolescents with ADHD for more than 60 years. Considering recent publications on methylphenidate for ADHD, we here give an overview of its effects in children and adolescents with ADHD, elicited by a well-disputed Cochrane review and narratively synthesise the evidence in the field. Method: We searched for systematic reviews and meta-analyses that investigated methylphenidate as an intervention for children and adolescence with ADHD compared with placebo or no treatment. We assessed the quality of the evidence using AMSTAR II. Results: We found 24 eligible systematic reviews and meta-analyses of which 11 were rated as high- quality evidence according to AMSTAR II. The evidence claiming that methylphenidate is beneficial in treating children and adolescents with ADHD was of very low certainty. The underreporting of adverse events in randomised clinical trials may impede an adequate depiction of the balance between benefits and harms. Conclusions: It appears that there is uncertain evidence on group-level to support the claim that methylphenidate is beneficial in treating children and adolescents with ADHD. Future randomised clinical trials and systematic reviews should include individual participant data, which would allow us to assess intervention effects across modifiers, like age, sex, ADHD subtypes, comorbidities, and dose.